Managing the liberalization of Italy's retail electricity market: A policy proposal☆. (February 2020) - Stagnaro, Carlo; Amenta, Carlo; Di Croce, Giulia; Lavecchia, Luciano
Abstract: Italy will phase out electricity retail price regulation by July 1st, 2020. Until then, residential customers and small businesses who do not choose their supplier are served under a regulated tariff named "maggior tutela" (greater protection), supplied by the local distributor at a price set by the regulator. We review the literature on electricity retail competition – with particular regard to its expected effects on prices, innovation, and customer engagement – and the conditions under which competition is expected to deliver benefits. We perform a Structure-Conduct-Performance analysis of Italy's retail electricity market for residential customers, finding two issues potentially problematic: excessive market concentration and low customer engagement. We propose a phase-out mechanism that relies on graduality, asymmetric regulation, and a mandatory, opt-out collective switching exercise. The mechanism aims to rapidly reduce market concentration by leveraging behavioral incentives to customers to switch to the cheapest supplier. Highlights: Italy started the liberalization of the retail electricity market in 1999. Customers have been free to switch supplier since July 2007. The regulated regime will be phased out by July 2020. There is a risk that the incumbent might reap the benefits from liberalization. A phasing out process based on collective switching may prove effective.